Changes in the Brain : Impact on Daily Life - Chiaravalloti, Nancy D.; Goverover, Yael (Springer New York : Imprint: Springer, 2017)
This informative text details the many changes in everyday life as the result of injury, illness, or aging affecting the brain. Experts across brain-related fields trace mechanisms of conditions such as Parkinson's disease, TBI, and dementia as they impact regions of the brain, and resulting cognitive, emotional, sensory, and motor impairments as they contribute to deficits in personal and social functioning. In addition to symptoms and behaviors associated with insults to the brain (and the extent to which the brain can adapt or self-repair), chapters provide cogent examples of how societal and cultural expectations can shape the context and experience of disability. The book's focus on everyday activities brings new clarity to diverse links between symptoms and diagnosis, brain and behavior. Included in the coverage: ·The aging brain and changes in daily function. ·Stroke: impact on life and daily function. ·Traumatic brain injury (TBI) and the impact on daily life. ·Everyday life with cancer. ·Real-world impact of HIV-associated neurocognitive impairment. ·Disability and public policy in America. ·Living after brain changes, from the patient's perspective. Rich in empirical data and human insight, Changes in the Brain gives neuropsychologists, clinical psychologists, clinical social workers, and rehabilitation nurses a robust new understanding of the daily lives of patients, both in theory and in the real world.- Resumé vydavatel
Keywords: mozek; nemoci mozku; poranění mozku; neuropsychologie; brain; brain diseases; brain injuries; neuropsychology; elektronické knihy; sborníky; electronic books; papers of several authors